DESCRIPTION OF MOTHER AND CHARACTERISTICS OF MOTHER WHO HAVE A BABY AGE 6-11 MONTHS ABOUT VITAMIN A IN PAMEKARAN VILLAGE - Antri Ariani; Siti Ayu Srimuningsih; Andria Pragholapati (JURNAL KEBIDANAN, 2021)
One indicator of the success of development in the health sector can be seen from the level of maternal and infant mortality rates. One cause of death in infants and toddlers is neurological diseases including eye disease. Around the world among preschoolers there are an estimated 6-7 million cases of xerophthalmia each year, approximately 10% of them suffer from corneal damage. Among those who suffered corneal damage 60% died within one year, 25% became blind and 50-60% were half blind. This is caused due to lack of vitamin A in a child's body. To combat VAD in Indonesia, especially in infants (6-59 months) the Indonesian Ministry of Health has collaborated with Helen Keller Indonesia (IPR) by administering high doses of vitamin A capsules to infants, toddlers and postpartum mothers. This study aims to determine the description of the attitude of mothers who have babies 6-11 months about vitamin A in Pamekaran village (conducted in April-June 2019). The design used is descriptive research. With the data obtained through the collection of questionnaire data from mothers who have babies 6-11 months. Data is presented in the form of frequency distribution with univariate analysis. With a population of 445 people, and a total sample of 82 people with a simple random sampling technique. The results showed that more than half of respondents had negative attitudes namely 61%. Characteristics of mothers who have babies aged 6-11 months are half aged 21-35 years which is as much as 68.3%, more than half are high school educated at 73.2% and more than half are multipara at 70.7%. Thus it can be concluded that more than half of the respondents have negative attitudes, aged 21-35 years, multigravida and high school graduates. Therefore it is expected that health workers will further enhance IEC about vitamin A and also more vigorously sweeping or giving vitamin A door-to-door.